Exploring Digital Platform Adoption: An Using Extended UTAUT2 Approach with Environmental Turbulence as a Moderating Variable - Adi Pradana Hidayat; Wuryan, Wuryan Andayani; Ainur, Ainur Rofiq (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to examine digital platforms adoption in the Malang city culinary industry by using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach with environmental turbulence as moderator. Methodology/approach: Primary data is collected from 413 micro and small business owners in Malang through questionnaires. The data was analyzed using the Partial Least Square (PLS) statistical technique to test the relationship between variables. Findings: The results of this study indicate that the adoption of digital platforms in the Malang City culinary industry is influenced by performance expectancy, social influence, hedonic motivation, price value, and habit, all of which drive an increase in behavioral intention. Conversely, effort expectancy and facilitating conditions do not influence behavioral intention. Furthermore, facilitating conditions, habit, and behavioral intention influence digital platform adoption. Moderator analysis shows that environmental turbulence plays varied roles in shaping user adoption. Environmental turbulence strengthens the impact of performance expectancy on individuals’ intention to adopt a digital platform. Conversely, its moderating effect is reversed when it interacts with habit in predicting digital platform adoption. The study also reveals that environmental turbulence does not moderate the relationship between price value and behavioral intention. Practical implications: This study confirms that culinary businesses need to maximize digital platforms by improving the benefits, efficiency and reliability of their services. Marketing based on social influence, customer reviews and community collaboration is important to attract users. The user experience needs to be enhanced through attractive design and loyalty programs. Businesses must also maintain service quality and ease of access to ensure continued use. In an unstable environment, technology must be utilized as an adaptation tool to improve resilience and speed of response to market changes. Originality/value: This study adds the moderating variable of environmental turbulence, which is believed to have a combined effect on the relationship between exogenous and endogenous variables, with the aim of addressing the inconsistency of previous research findings. This study also uses questionnaires distributed to micro and small businesses in Malang City, thereby producing research findings that are relevant to current conditions.